Germination of True Shallot Seed (TSS) of Onion Cultivars and Mixing of Planting Media - Sopiana, Rina; Suwignyo, Rujito Agus; Harun, M. Umar; Susilawati, Susilawati (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2023)
In Indonesia, onion cultivation uses bulbs, which disrupts stocks of consumtion and trade quite significantly. One way to reduce the need for bulbs from onions is to use True Shallot Seed (TSS). Onion of TSS can reduce production costs, and is practical in shipping compared to bulbs. One of the activities in the cultivation of TSS is the preparation of strong, uniform and healthy of seedling. This study aims to examine the appropriate composition of organic matter as a planting medium to accelerate the germination time of various cultivars of TSS. The planting medium tested was a mixture of soil, rice husk, cocopeat and sawdust. This study used a complete randomized block design which was arranged in factorials. The first factor was the variety and the second factor was mixing of organic matter. Mixing organic matter with the soil before planting onion seeds led to an increase in soil pH from 0.77 to 1.51. Mixing soil with organic matter before implementation increased the pH of the media, CEC, WHC, and decreases the bulb density. After germination, the husk and cocopeat mixture showed a pH (5.9), CEC (1.62 mS.cm-1), bulb density (0.3 g/cm3) and WHC (162%). The combination of rice husk and cocopeat as the growing medium (4,9 days), the Sanren cultivar (7,3 days) exhibited the fastest germination and seedling growth rate compared to other cultivars and mixed growing media.